The Stuff of Thought: Language as a Window into Human Nature, by Steven Pinker - Lotte Meteyard (Opticon1826, 2009)
The Stuff of Thought (2007) is Steven Pinker’s fifth popular science book, designed to complete two different trilogies that explore language, the mind and human nature. All his books have, in some way, explored the nature-nurture debate: are we primarily products of our genes or products of our environment? In his first popular science book, The Language Instinct (1994), Pinker made the case for an innate language capacity: language is not learned in its entirety, much of it (particularly grammar) is already present in the determined structure of our mind/brain. In Words and Rules (1999), the regular (‘bake – baked’) and irregular (‘buy – bought’) forms of the past tense were used to explore how language might be represented in the mind; Pinker presents a middle way between the rationalists (who state that ‘the mind has innate concepts’) and the empiricists (‘the mind is a blank slate’), with regular forms created by the application of an innate rule (rationalism) and irregular forms created through memorization (empiricism). These books were the first two in the ‘language and the mind’ trilogy. The other trilogy, beginning with the two books How the Mind Works (1997) and The Blank Slate (2000), deals with human nature. In both books, Pinker argues for innate cognitive abilities that are common across all human beings, and offers a psycho-evolutionary definition of human nature. Reviews of Pinker’s books are always mixed, reflecting the fact that there is still disagreement in popular culture and in the scientific community on the nature-nurture debate (aside from the common understanding that human nature is some mixture of the two). Pinker’s position represents an ideological attachment to nature and evolutionary design, and it often has a teleological narrative in which humans fulfil their impressive biological potential in the (somewhat under-described) world.